Study on safe utilization technology model of high acidity and mild cadmium-contaminated paddy fields: a case of the cadmium-contaminated pilot area in Yongkang City of Zhejiang Province - CHEN Simin; LU Xinzhe; HUANG Chunlei; SHI Jiachun; XU Jianming (浙江大学学报. 农业与生命科学版, 2023)
In the highly acidic soil pilot area contaminated by cadmium (Cd) in Yongkang City of Zhejiang Province, we screened low-Cd-accumulating rice cultivars and soil passivators in the field and performed the combined effect tests for two consecutive years to explore the safe utilization technology model suitable for local Cd-polluted paddy fields. The results showed that ‘Xiushui 519’ (XS519), ‘Zhenuo 106’ (ZN106), ‘Zhongzheyou 1’ (ZZY1H) and ‘Zhongjia 8’ (ZJ8H) could be recommended as low-Cd-accumulating rice cultivars suitable for local planting. Among them, ‘Xiushui 519’ had the lowest and most stable Cd accumulation ability, and the average bioconcentration factors (BCFs) of Cd in the rice grains in the two years were 0.090 and 0.159, respectively; in the screening tests of passivators, the improvement effect of lime (L) on soil pH was significant. Lime, iron-modified biochar (FeC) and calcium-magnesia phosphate fertilizer (CaMgP) could reduce soil available Cd contents to a certain extent (passivation rates were 14.8%, 7.1% and 6.9%, respectively). In addition, 1 800 kg/hm2 iron-modified biochar and 2 400 kg/hm2 soil conditioner had better effects on reducing the Cd content in the rice grains of ‘Zhongjia 8’, which decreased by 32.2% and 29.0%, respectively, after application. According to the results of the combination tests of the low-Cd-accumulating cultivars and passivators, both the application of 2 250 kg/hm2 iron-modified biochar and 2 250 kg/hm2 soil conditioner increased obviously the soil pH values at the tillering stage and filling stage, the soil conditioner of which had a better improvement effect. The Cd contents in the rice grains of ‘Xiushui 519’ and ‘Zhenuo 106’ were extremely significant correlations with the soil pH values (5.19-5.61) at the mature stage. Within the range of soil pH values involved in the test, except for the combination of ‘Xiushui 519’ and the 1 500 kg/hm2 soil conditioner, the Cd content in the rice grains increased with increasing application amount of passivators. Therefore, planting ‘Xiushui 519’ (a low-Cd cultivar) directly is the best choice for the safe utilization of Cd-contaminated paddy fields in this area, which is both economical and convenient.